OPTIMIZATION OF CORPORATE COMPLIANCE PROCEDURES IN THE PAYMENT OF BPJS KETENAGAKERJAAN CONTRIBUTIONS IN JAMBI - Dela, Selfi; Putra, Wirmie Eka (Jambi Accounting Review (JAR), 2025)
This study aims to analyze company compliance procedures in paying contributions to BPJS Ketenagakerjaan Jambi Branch and identify obstacles in the collection process. Using a descriptive qualitative method, data were collected through participatory observation during the internship period (February–April 2025), interviews, and documentation studies. The results indicate that BPJS Ketenagakerjaan Jambi Branch has implemented systematic compliance procedures through socialization, administrative collection, and field visits. Digital systems such as SIPP and EPS improve data accuracy and facilitate payments. However, challenges remain due to company financial constraints and low awareness of regulatory obligations. Cooperation with the Prosecutor’s Office serves as a final enforcement mechanism to create a deterrent effect for contribution defaulters. Overall, compliance procedures have been implemented in accordance with regulations, although stronger supervision is still required to reduce contribution receivables and ensure workers’ protection rights.